POLICY IMPLEMENTATION LOCAL GOVERNMENT INFORMATION SYSTEM (SIPD) IN SOUTHEAST MALUKU MALUKU PROVINCE - Riandy Imanuel Ohoira; Ismail Nurdin; Widodo Sigit Pudjianto (Sean Institute, 2023)
This study aims to determine and analyse the process of local government information system (SIPD) policy implementation with in the Southeast Maluku Regency Government. Using Merilee S. Grindle policy implementation theory as an analytical tool for the implementation of SIPD with the policy content dimension including indicators of interests affected, types of benefits, extend of change envisioned, site of decision making, program implementors and resources commited, then the implementation context dimension includes indicators power, interest, and strategy of actor involved, institution and regime, and compliance and responsiviness. Furthermore, it describes the barriers to implementing SIPD in Southeast Maluku Regency, and the efforts made to overcome the existing barriers. The method used in this research is descriptive research design with a qualitative approach, with researchers as research instrument, data collection technigues using interviews, documentation and observation, data analysis through reduction, presentation and conclusion drawing supported by triangulation for data validity. The result of this study indicate that the process of implementing the regional government system (SIPD) policy in Southeast Maluku Regency could have gone better. This is because there are still several obstacles found, namely the low quality of the competence pf programme implementers, inadequate facilities and infrastructure resources, and low level of compliance and response from implementers, as well as efforts that have been made by local government to overcome obstacles to the implementation of SIPD in Southeast Maluku Regency.